Criteria for the Identification and Management of Domino Effects: an Approach to the Area Risk Evaluation - Romualdo Marrazzo; Alberto Ricchiuti (Chemical Engineering Transactions, 2025)
The paper presents a set of technical and operational criteria provided for the identification and management of domino effect by the Competent Authorities, with the consequent necessity of elaborating a specific area risk evaluation in case of high concentration of industrial establishments. The approach foresees: 1. preliminary identification of establishments potentially affected by domino effects; 2. exchange of information, between establishments operators, needed to: review the actual potential of domino effects and, in case, the accident analyses; estimate effects on equipment; provide, if domino scenarios are identified, for additional measures to prevent and mitigate the scenarios; 3. domino establishments final identification. Domino effects need to be considered due to their potential for risk escalation associated with the events chain, through an increase in the likelihood of a major accident or the potential consequences. These results must be considered in the internal emergency procedures of the establishments potentially involved, in the area external emergency plan and consequently integration of the safety requirements for land use planning, and information to potentially involved public in the nearby area. The domino effect analysis also plays a main role in the context of an evaluation of the overall risk in an industrial area with the presence of many hazard sources, being a necessary stage for preparing a quantitative area risk study. In these sites, it is necessary to evaluate the significance of an aggravation of the risk based on the possible peculiarities of the site where the industrial plants are located, such as the presence of vulnerable territorial elements in the damaged areas around each establishment.Among sources of risks, an increasing role will play in the NaTech events, also due to ongoing climate changes. Therefore, it is necessary, while identifying the hazards and assessing the major risks of industrial sites, to pay attention to the natural hazards that may affect them, also considering the multiple simultaneous scenarios that they may trigger, giving a relevant contribution to the overall risk in an industrial area. Keywords: domino; Seveso; major accidents; threshold; area risk; N